2022
DOI: 10.1242/jeb.244560
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone-induced cell death in sea urchin metamorphic development

Abstract: Thyroid hormones (THs) are important regulators of development, metabolism, and homeostasis in metazoans. Specifically, they have been shown to regulate the metamorphic transitions of vertebrates and invertebrates alike. Indirectly developing sea urchin larvae accelerate the formation of juvenile structures in response to thyroxine (T4) treatment, while reducing their larval arm length. The mechanisms underlying larval arm reduction are unknown and we hypothesized that programmed cell death (PCD) is linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Previous research has shown that THs induce apoptosis in sea urchins (38) and that the histaminergic system may be crucial for regulation of metamorphosis and settlement, with histamine accelerating metamorphic competence but inhibiting settlement and apoptosis in the larval arms (52,122). We find that in postrudiment larvae (27d), T4 significantly increased histamine receptor expression, while in pre-rudiment larvae (23d), T4 increased expression of histamine-metabolizing enzymes.…”
Section: Neuronal Signaling and Crosstalkmentioning
confidence: 43%
See 2 more Smart Citations
“…Previous research has shown that THs induce apoptosis in sea urchins (38) and that the histaminergic system may be crucial for regulation of metamorphosis and settlement, with histamine accelerating metamorphic competence but inhibiting settlement and apoptosis in the larval arms (52,122). We find that in postrudiment larvae (27d), T4 significantly increased histamine receptor expression, while in pre-rudiment larvae (23d), T4 increased expression of histamine-metabolizing enzymes.…”
Section: Neuronal Signaling and Crosstalkmentioning
confidence: 43%
“…Apoptosis in particular plays an important role in morphogenesis during sea urchin larval development (38,(99)(100)(101). We previously found that THs regulate larval arm retraction via programmed cell death in sea urchin larvae, with increased levels of caspase 3/7 activation and apoptosis (38). In this transcriptome analysis, we find that caspase gene expression was not affected by THs.…”
Section: Regulation Of Other Functional Groups By Thyroid Hormones 43...mentioning
confidence: 58%
See 1 more Smart Citation
“…Taylor and Heyland (2017) suggested that sea urchin skeletogenesis is regulated by thyroid hormones via a non-genomic integrin-mediated MAPK cascade triggered by direct TH binding to skeletogenic mesenchyme cells. Additionally, Wynen et al (2022) demonstrated a role for THs regulating apoptosis in metamorphic development. However, it is unclear if TH signaling and its involvement in skeletogenesis is limited to S. purpuratus larvae, or if it can be generalized to other sea urchins and echinoderms.…”
Section: Introductionmentioning
confidence: 99%
“…T4 has been shown to accelerate metamorphic development in echinoderms and molluscs (Carpizo-Ituarte, 1993; Chino et al, 1994;Fukazawa et al, 2001;Heyland et al, 2004Heyland et al, , 2006Hodin et al, 2001;Johnson, 1998;Johnson & Cartwright, 1996;Saito et al, 1998). Evidence suggests that these mechanisms may rely on the nuclear hormone receptor-mediated pathway (Huang et al, 2015;Taylor et al, 2023) and that THR may regulate apoptosis and skeletogenesis in sea urchins (Taylor et al, 2023;Wynen et al, 2022). Additionally, embryonic and larval sea urchin skeletogenesis may be regulated by the TH integrin-mediated pathway (Taylor & Heyland, 2018).…”
Section: Introductionmentioning
confidence: 99%